Clinical and Biological Significance of a Necroptosis-Related Gene Signature in Glioma - Zhou, Zunjie; Xu, Jing; Huang, Ning; Tang, Jun; Ma, Ping; Cheng, Yuan (Frontiers in Oncology, 2022)
Background: As a novel form of programmed cell death, necroptosis has been established to relate to multiple tumors and their immune microenvironment, while the association with glioma has not been clarified. Methods: Necroptosis genes were obtained from the GSEA database. The RNA-seq and clinical data were downloaded from TCGA and CGGA databases. By univariate and multivariate Cox regression analysis, a necroptosis gene signature was constructed. Next, the survival analysis, independent prognosis analysis, and Nomogram were performed to assess and verify the model. Subsequently, we analyzed the tumor microenvironment (TME) and immune cells infiltration via ESTIMATE and CIBERSORTx algorithm. Finally, the response of glioma patients to immune checkpoint inhibitor (ICI) therapy was calculated by the database TIDE. Results: Of seven prognostic necroptosis genes, RIPK1, RIPK3, FAS, and FADD were identified to construct the risk signature, which can forecast the prognosis of glioma individuals accurately. The results of functional enrichment suggested that necroptosis was correlated with immune response and angiogenesis. Immune analysis revealed that necroptosis could boost the immune activity and attract immunosuppressive cell infiltration to form a chronic inflammatory microenvironment, promoting the growth of glioma. Additionally, the TIDE showed that the glioma population with high necroptosis genes expressed had a better response to ICI treatment. Finally, we verified the expression of risk signature genes between normal and glioma tissue by IHC. Conclusion: We constructed a necroptosis genes signature, which had the potential to be an underlying biomarker for predicting prognosis, revealed the association of necroptosis with the immune microenvironment, and served as reference for immune therapy.